Tea saponin additive to extract eleutheroside B and E from Eleutherococcus senticosus by ultrasonic mediation and its application in a semi-pilot scale - Xinyu Yang; Tingting Liu; Shuwen Qi; Huiyan Gu; Jialei Li; Lei Yang (Ultrasonics Sonochemistry, 2022)
The safety of ethanol in operations and its effects on human health are gradually being questioned. Under this premise, we attempted to use the natural surfactant tea saponin, which originates from the processing residues of camellia oil, as the additive of the extraction solvent and to extract eleutheroside B and eleutheroside E in the roots and rhizomes of E. senticosus by ultrasonic mediation. After a single-factor experiment, extraction kinetics at different powers and reaction temperatures, and Box–Behnken design optimization, the optimal conditions obtained were 0.3% tea saponin solution as the extraction solvent, 20 mL/g liquid–solid ratio, 250 W ultrasonic irradiation power (43.4 mW/g ultrasonic power density) and 40 min ultrasonic irradiation time. Under optimal conditions, satisfactory yields of eleutheroside B (1.06 ± 0.04 mg/g) and eleutheroside E (2.65 ± 0.12 mg/g) were obtained with semi pilot scale ultrasonic extraction equipment. The experiments showed that compared with the traditional thermal extraction process, the extraction time is significantly reduced at lower operating temperatures.